Concise synthesis of (+)-deoxoprosophylline via Co(III)(salen)-catalyzed two stereocentered HKR of racemic azido epoxides - Devalankar, Dattatray A.; Sudalai, Arumugam (Tetrahedron Letters, 2012)
An efficient synthesis of (+)-deoxoprosophylline has been achieved in high optical purity (99% ee) from readily available cis-2-butene-1,4-diol. The strategy employs Co-catalyzed Hydrolytic Kinetic Resolution (HKR) of two stereocentered racemic azido epoxides and diastereoselective intramolecular reductive cyclization as key reactions. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Azido epoxide; Hydrolytic kinetic resolution; Piperidine; Wittig olefination

Formal asymmetric synthesis of (2S,4R)-4-hydroxypipecolic acid via Co(III)(salen)-catalyzed two stereocentered HKR of racemic azido epoxide - Kamble, Rohit B.; Gadre, Shubhankar Haribhau; Suryavanshi, Gurunath M. (Tetrahedron Letters, 2015)
An efficient formal synthesis of (2S,4R)-4-hydroxypipecolic acid has been achieved in high optical purity (99% ee) from readily available benzaldehyde. The strategy employs an iodine-induced intramolecular cyclization of a carbonate and Co-catalyzed Hydrolytic Kinetic Resolution (HKR) of two stereocentered racemic azido epoxide as the key reactions to construct chiral 1,3-amino alcohol functionality. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Azido epoxide; Hydrolytic kinetic resolution; lodocyclization; Piperidine

Enantioselective synthesis of (+)-Sedridine, (-)-Allosedridine and their N-Methyl analogs via Maruoka-Keck allylation and CBS reduction - Bhoite, Shubhangi P.; Suryavanshi, Gurunath (Natural Product Research, 2023)
A simple synthetic approach has been developed for the enantioselective total synthesis of (+)-Sedridine, (-)-Allosedridine and their analogs such as (+)-N- Methyl Sedridine and (-)-N-Methylallosedridine. The synthesis was achieved by using commercially available starting materials via Maruoka-Keck allylation, Wacker oxidation, and CBS reduction. The synthetic root provides a good diastereomeric ratio and high yields.
Keywords: CBS reduction; Maruoka-Keck allylation; Piperidine; Wacker oxidation